1998
DOI: 10.1016/s0892-0362(97)00091-3
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects on Cognitive Functioning in 9- to 12-Year Olds Prenatally Exposed to Cigarettes and Marihuana

Abstract: Cognitive performance was examined in 131 9-12-year-old children for whom prenatal marihuana and cigarette exposure had been ascertained. The subjects, participants in an ongoing longitudinal study, were from a low-risk, predominantly middle class sample. The tasks included the WISC-III and a series of tests assessing aspects of cognition subsumed under the rubric of executive function. Consistent with results obtained at earlier ages, discriminant function analysis revealed a dose-dependent association, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
171
1
3

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 231 publications
(191 citation statements)
references
References 36 publications
13
171
1
3
Order By: Relevance
“…The studies outlined in Table 1 (25). Seven studies examined the relationship of postnatal exposure to smoke and performance on a range of cognitive, perceptual, central auditory, and linguistic abilities (27,29,(34)(35)(36)(37)(38). Of the six studies that controlled for prenatal maternal smoking (27,(34)(35)(36)(37)(38), half (27,36,37) show clear decrements associated with postnatal ETS exposure.…”
Section: Behavioral Assessmentmentioning
confidence: 99%
See 3 more Smart Citations
“…The studies outlined in Table 1 (25). Seven studies examined the relationship of postnatal exposure to smoke and performance on a range of cognitive, perceptual, central auditory, and linguistic abilities (27,29,(34)(35)(36)(37)(38). Of the six studies that controlled for prenatal maternal smoking (27,(34)(35)(36)(37)(38), half (27,36,37) show clear decrements associated with postnatal ETS exposure.…”
Section: Behavioral Assessmentmentioning
confidence: 99%
“…Postnatal ETS exposure has also been associated with behavioral problems in all three studies that specifically examined behavior problems in children (31,32,40) and adequately controlled for home environment and other potentially intervening factors; two of these three studies (32,40), however, showed larger associations between behavioral problems and prenatal exposure to maternal smoke than with postnatal child ETS exposure. There are only three studies that investigated the relationship of maternal ETS exposure during pregnancy (28,36,38) and general cognitive performance, two of which were on the same cohort. The first study on the Ottawa cohort reported adverse cognitive effects of maternal ETS exposure during pregnancy as strong as those for active smoking (28) but did not take into account postnatal exposure, whereas the second study (38) showed no relationship between maternal ETS exposure during pregnancy among nonsmokers and general cognitive performance in their children.…”
Section: Behavioral Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Prospective clinical studies have linked prenatal exposure to tobacco smoke to reductions in motor and verbal comprehension scores in children assessed at 13 months of age (Gusella and Fried, 1984), reductions in measures of language development, and general intellectual function in children assessed at 3, 4, 5, and 6 years of age (Fried and Watkinson, 1990;Fried et al, 1992), deficits in verbal and nonverbal learning and memory in preadolescents (Cornelius et al, 2001), and reductions in general intelligence in children assessed between 9 and 16 years of age (Fried et al, 1998(Fried et al, , 2003.…”
Section: Introductionmentioning
confidence: 99%